Community-Based Halal Tourism as a Model of Social Da'wah: Sustainable Development in the Inhabited Islands of Kepulauan Seribu, Indonesia - Nursyahid, M; Haryanti, Ely; Arnoldy (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study analyzes the potential, challenges, and strategies for developing community-based halal tourism on the inhabited islands of Kepulauan Seribu from a sustainable tourism perspective. Using a mixed methods approach with 200 respondents across four islands (Tidung, Pramuka, Harapan, Pari), this research finds that despite strong stakeholder support (84% community members, 89% business operators) and significant market potential, halal tourism implementation faces substantial challenges including limited infrastructure, inadequate understanding of the concept, minimal halal certification (7.4% homestays, 23% food stalls), and overtourism issues that exceed carrying capacity by up to 300% during peak seasons. The analysis reveals that only 34% of respondents comprehensively understand halal tourism beyond food and places of worship. The research recommends an integrated development model with five pillars: institutional framework and regulations, human resource capacity building, sustainable infrastructure, spiritual-conservation tourism product innovation, and digital marketing. This model has the potential to increase tourism revenue by IDR 36.75-61.25 billion per year while preserving the environment and empowering local communities, positioning Kepulauan Seribu as a model for sustainable small island halal tourism in Indonesia.